Choral connections : Mixed voices (level 4) - Tower, Mollie G.; Pullen, Milton; Steele, Ken.; Stephens, Gloria J. (New York : Glencoe/McGraw Hill, 1999)
Choral Connections is a four-level series designed to build music literacy and promote vocal development for students ... in grades 6-12. Choral Connections presents beginning, intermediate, and advanced-level literature for various voice groupings: mixed, treble, and tenor-bass." (p. T8 Mixed voices, teacher's wraparound edition
Includes glossary.
Keywords: Choral connections; Music; Choral singing -- Juvenile. -- Instruction and study